Analysis of creative approaches in digital marketing for the lisweet patisserie cake shop business in samarinda - Christie Stephanie P; Della Olivia Caterina K; Marina Angreani; Rahma Avrida Olivia M; Putri Ella Faradillah (Enrichment : Journal of Management, 2026)
The development of digital technology encourages micro-enterprises in the culinary sector to adopt digital-based marketing strategies. This study analyzes the effectiveness of creative digital marketing in improving the competitiveness and viability of micro-enterprises. Using a qualitative descriptive approach through in-depth interviews and observation, the analysis focuses on marketing, operations, human resources, legal aspects, and investment. The findings show that social media platforms such as Instagram and Shopee Food, along with collaboration with content creators, effectively expand market reach, enhance customer interaction, and strengthen brand awareness. The study highlights the integration of digital creativity and business feasibility in the culinary sector